Temporary Endobronchial Stent as a Bridge to Corrective Surgery For Severe Kyphoscoliosis-associated Central-Airway Extrinsic Compression. Issue 4 (October 2016) - Sriratanaviriyakul, Narin; Nguyen, Lam-Phuong; Ismail, Heba; Roberto, Rolando F.; Yoneda, Ken Y.
Abstract : Kyphoscoliosis is known to compromise lung function, with the primary mechanism being reduced chest wall compliance with a resultant restrictive pulmonary physiology. Severe scoliosis can also cause extrinsic compression of the central airways, leading to recurrent respiratory infections, lobar atelectasis, and potentially acute respiratory failure. Definitive therapy is corrective surgery of the spine. However, patients with severe scoliosis are at a potentially high risk of perioperative pulmonary complications. To our knowledge, we report the first successful use of retrievable endobronchial stents as a bridge to corrective surgery for kyphoscoliosis-associated complete central-airway extrinsic compression in a patient who was considered as too high risk for surgical correction due to her respiratory status. After surgery, the stents were removed and our patient experienced sustained improvement in pulmonary function and the clinical respiratory status.